RESEARCH ON CRYSTAL PLASTICITY CONSTITUTIVE MODEL CONSIDERING THE STRAIN SOFTENING EFFECT OF ULTRA-FINE GRAIN METAL MATERIALS - ZHENG Zhanguang; FAN Jianan; SUN Teng; XIE Changji; HUANG Zeng (Jixie qiangdu)
In order to study the strain softening phenomenon of ultra-fine grain (UFG) metal materials under uniaxial tensile loading, a modified model considering the effect of residual internal stress was proposed based on the classical crystal plasticity constitutive model, and the specific form of residual internal stress and its evolution were programmed into the user subroutine. The uniaxial tensile test data were fitted to verify the validity of the model, and the finite element simulation results of crystal plasticity were compared with and without the residual internal stress. The results show that the simulation results obtained by using the modified crystal plasticity constitutive model are in good agreement with the experimental results, indicating that the modified crystal plasticity constitutive model can effectively capture the strain-softening phenomenon of UFG metal materials, and the simulation results show different properties under the two conditions whether the residual internal stress is taken into account. It is reasonable to explain the strain softening phenomenon of UFG metal materials from the perspective of the formation and action of residual internal stress.